An Analysis Of Slang Words Used In Social Media - siti frastiwi; Siti Aisyah (JournEEL, 2022)
In the area of language, slang is a phenomena of employing linguistic variations that form as a result of language development and a social dynamic in society. In Indonesian, slang is known as bahasa gaul, and it is primarily utilized by young people while conversing with others. As a result, the purpose of this study is to examine the form, function, and meaning of existing slang, particularly as it is employed on social media. The data collection methods used in this study are qualitative. The information was gathered through observations of the usage of slang in various social media platforms, after which the slang was classed according to the type and construction of words. According to the findings of Allan and Burridge (2006), the forms of slang seen on social media are particularly diversified, creative, and dynamic, including Fresh and Creative, Flippant, Imitative, Acronyms, and Clipping.